Low-Tech Game-Based System to Train Logical Reasoning: a technological prospection - Hora, Kaline Tatiane Passos da (2023)
Technological development has brought to society the possibility of access to technologies previously restricted to groups with great economic power. This popularization led to the need to learn and understand the logic of programming. This work carried out a technological prospection to verify the types of technology with the use of low-tech systems that are being developed for the learning of logical reasoning aimed at programming logic. The search strategies were defined based on keywords and codes International Patent Classification (IPC) and Cooperative Patent Classification (CPC) using the patent databases of Espacenet and the National Institute of Intellectual Property (INPI) during the year 2021. The results showed that systems for learning logical reasoning aimed at programming logic have been patented since 1916 and the evolution of video game consoles had a great influence on the evolution of games.